Exploring the contribution of the design characteristics of Information Systems' user interface to the adoption process. (18th May 2009) - Seneler, Cagla Ozen; Basoglu, Nuri; Daim, Tugrul
Today, the user interface component of Information Systems (ISs) is attracting great attention, being improved continuously and contributing more to the success of technology adoption. Even though the user interface is deemed to be the tip of the iceberg, the capability of the user interface adds a lot to the Information Technology (IT) adoption process. This paper aims at developing a better understanding of the interface design characteristics and technological architecture that affect smoother user adoption. The authors investigated the technology adoption characteristics by performing a qualitative analysis that included semistructured in-depth interviews. A total of nine IS users and five IS developers participated in the study. Many interface design characteristics that are evaluated in the literature were also considered. This paper also presents a technology adoption taxonomy for classifying the factors that influence user technology adoption. The findings of the interviews, the proposed technology adoption taxonomy and the implications of these findings are discussed. Also, further research opportunities are described.